Assessment of divertor heat load with and without external magnetic perturbation. (9th May 2017) - Sieglin, B.; Eich, T.; Faitsch, M.; Herrmann, A.; Kirk, A.; Scarabosio, A.; Suttrop, W.; Thornton, A.
Abstract: Divertor heat load is a major concern for large scale fusion devices such as ITER. Both steady state heat exhaust as well as heat loads due to transient events such as type-I ELMs need to be understood in order to predict the thermal load onto the divertor targets. The use of external magnetic perturbation to mitigate the ELM induced divertor load has been subject to a multitude of studies. In this study the influence of external magnetic perturbation on the SOL heat transport in ASDEX Upgrade L-Mode is shown. It is found that the heat transport perpendicular to the magnetic field is, within the uncertainty, unaffected by external magnetic perturbation. The influence of external magnetic perturbation on the ELM deposited energy density is shown. A scaling coupling the ELM deposited energy density on the divertor target with the upstream pedestal pressure is available. This scaling is able to describe the observed reduction of the ELM deposited energy density with external magnetic perturbation as a loss in pedestal pressure.